On the regioselective molecular sieves-promoted oxidative three-component synthesis of fused-benzimidazoles from $β $-ketoesters - Martin, Anthony; Cheshmedzhieva, Diana; Palermo, Valeria; Liéby-Muller, Frédéric; Romanelli, Gustavo P.; Gaudel-Siri, Anouk; Coquerel, Yoann; Constantieux, Thierry; Rodriguez, Jean (Comptes Rendus. Chimie)
The regioselectivity of molecular sieves-promoted oxidative three-component reaction between $β $-ketoesters, aromatic o-diamines and acrolein, leading to pyrido[1,2-a]benzimidazoles, has been investigated by a combination of experimental and theoretical studies. Molecular sieves act both as heterogeneous catalyst and dehydrating agent and their role has been modeled in the theoretical approach. The modulation of the reactivity of the aromatic diamine partner as a function of the nature of the substituents of the aromatic ring and its influence on the regioselectivity of the reaction could be rationalized.